Complex treatment of allergic eye diseases using interferon alfa-2b and loratadine gel for topical and external use - A. V. Surov,; A. G. Zaspina (Oftalʹmologiâ)
Aimis to determine the efficacy of Allergoferon® — combined medicine composed of interferon alfa-2b and loratadine gel for topical and external use — in ocular allergies treatment.Materials and methods. 60 patients with allergic eye diseases were treated. Allergoferon® gel applied QID on upper and lower eyelids was used as a first-line therapy. Efficacy was measured using the following criteria: chemozis, eyelid edema, conjunctival redness and discharge, the presence of conjunctival follicles and papillae. All symptoms were scored using a 4‑point scale (0 = none, 1 = mild, 2 = moderate, 3 = severe).Results. Topical administration of Allergoferon® was associated with significant symptoms reduction, i.e., chemozis by 82 %, eyelid edema by 91 %, conjunctival redness by 79 %, eyelid redness by 88 %, conjunctival discharge by 95 %, the presence of conjunctival follicles and papillae by 76 %.Conclusion. Allergoferon® gel for topical and external use quickly reduces tissue allergic reactions and, consequently, terms of treatment. This medication is highly-effective as a therapy of ocular allergies owing to its antihistamine, anti-inflammatory and anti-exudative effects.